Effect of Elevated Temperature on Bending Fatigue Behavior for Neat and Reinforced Polyamide 6,6 - Orhan Sabah Abdullah (مجلة النهرين للعلوم الهندسية, 2020)
Recently, considering polymer composite in manufacturing of mechanical parts can be caused a fatigue failure due to the very long time of exposure to cyclic loading and may at environmental temperatures higher than their glass transition temperature; therefore, in this paper, a comprehensive investigation for bending fatigue behavior at room and elevated temperatures equal to 60 °C, 70°C, and 80 °C will be done. Rotating bending test machine was manufactured for this purpose supplied with a connected furnace to perform fatigue tests at elevated temperatures. The obtained results appeared that the increase in applied stress and temperature caused a clear reduction in fatigue life; also the addition of carbon nanotubes enhanced the fatigue life at different temperatures by 183%, 205%, 218%, and 240%, respectively while the addition of short carbon fibers improved fatigue life by 324%, 351%, 387%, and 415%, respectively. As well as, Polyamide 6,6/carbon fiber composite appeared fatigue limit at temperatures equal to 20°C and 60°C and stresses approximately equal to 55 MPa and 38 MPa respectively.